Obscure Severe Infrarenal Aortoiliac Stenosis With Severe Transient Lactic Acidosis - Teerapat Nantsupawat MD; Charoen Mankongpaisarnrung MD; Suthipong Soontrapa MD; Chok Limsuwat MD; Kenneth Nugent MD (SAGE Publishing, 2013)
A 57-year-old man presented with sudden onset of leg pain, right-sided weakness, aphasia, confusion, drooling, and severe lactic acidosis (15 mmol/L). He had normal peripheral pulses and demonstrated no pain, pallor, poikilothermia, paresthesia, or paralysis. Empiric antibiotics, aspirin, full-dose enoxaparin, and intravenous fluid were initiated. Lactic acid level decreased to 2.5 mmol/L. The patient was subsequently extubated and was alert and oriented with no complaints of leg or abdominal pain. Unexpectedly, the patient developed cardiac arrest, rebound severe lactic acidosis (8.13 mmol/L), and signs of acute limb ischemia. Emergent computed tomography of the aorta confirmed infrarenal aortoiliac thrombosis. Transient leg pain and transient severe lactic acidosis can be unusual presentations of severe infrarenal aortoiliac stenosis. When in doubt, vascular studies should be implemented without delay to identify this catastrophic diagnosis.